Maqasid Ash-Shariʻah Framework and the Development of Islamic Finance Products: The Case of Indonesia - Abdul Qoyum (Tazkia Islamic Finance and Business Review, 2018)
The objective of this research is to discuss the concept of Maqasid ash-Shariʻah as well as to propose new concept of Maqasid ash-Shariʻah framemork that will give many benefit in Islamic financial product development. Using a qualitative approach and using literature review, this study concludes that, the purpose of sharia can be in the form of micro and macro as well. Both of these goals must be able to be realized by Islamic finance, primarily through its  products. In order to realize these two objectives, the process of the development of Islamic financial products is not only the concern of the sharia council, but also involving microprudential and macropruedential authorities. Therefore, here, the process of establishing Islamic financial products may involve Bank Indonesia, OJK, LPS, as well as DSN. The big goal is that every product can actually generate maslahah, both at micro and macro levels.